2012
DOI: 10.1007/s11046-012-9600-5
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of HOG-MAPK Pathway in Aspergillus fumigatus

Abstract: Aspergillus fumigatus is an important opportunistic fungal pathogen that causes lethal systemic invasive aspergillosis. It must be able to adapt to stress in the microenvironment during host invasion and systemic spread. The high-osmolarity glycerol (HOG) mitogen-activated protein kinase (MAPK) signaling pathway is a key element that controls adaptation to environmental stress. It plays a critical role in the virulence of several fungal pathogens. In this review, we summarize the current knowledge about the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 114 publications
0
49
0
1
Order By: Relevance
“…In A. fumigatus , two Hog1 orthologues, SakA and MpkC participate in response to oxidative and nutritional stresses, respectively [32]. In addition, A. fumigatus sakA also shares a conserved role in osmotic stress response as in S. cerevisiae such that A. fumigatus sakA controls the transcription of protein DprB required for osmotic and pH stress [33]. This indicates that overcompensation of P. marneffei atfA mutant strain to osmotic stress might come from the activation of the stress signaling pathway or transcription factor other than SakA-AtfA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In A. fumigatus , two Hog1 orthologues, SakA and MpkC participate in response to oxidative and nutritional stresses, respectively [32]. In addition, A. fumigatus sakA also shares a conserved role in osmotic stress response as in S. cerevisiae such that A. fumigatus sakA controls the transcription of protein DprB required for osmotic and pH stress [33]. This indicates that overcompensation of P. marneffei atfA mutant strain to osmotic stress might come from the activation of the stress signaling pathway or transcription factor other than SakA-AtfA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of MAP kinase involvement is bolstered by the reported direct phosphorylation of the targeting region of S. cerevisae Bcy1 by MPK1[16], homologous to A. fumigatus MpkA, a key regulator of the cell wall integrity (CWI) pathway [38]. This result thus suggests potential cross talk between the cAMP and CWI pathways, or possibly involvement of the high osmolarity glycerol response pathway, regulated by the MAP kinase SakA [39, 40]. Analysis of the hinge region cluster comprising T121, S122 and S124 produced moderate hits for both calcium/calmodulin-dependent protein kinase (CaM Kinase-II) and glycogen synthase kinase (GKS3) at all three sites (though in the case of S122 the strongest prediction was for PKA, as expected).…”
Section: Discussionmentioning
confidence: 99%
“…The HOG signaling pathway plays a crucial role in the virulence of several fungal pathogens such as Aspergillus fumigatus and Canida albicans, because it regulates morphogenesis in fungi (Ma and Li 2012). It has been observed that C. albicans virulence diminishes by the inactivation of some elements of diverse stress responses, including Hog1, which has led to the suggestion that its virulence has evolved in parallel with the response to different stress situations (Brown et al 2014).…”
Section: Yeast and Fungimentioning
confidence: 99%
“…Hence, the details of signal transduction under osmotic stress in C. albicans remain unresolved. Although 3 HKs are present in C. albicans, which are needed for hyphal formation and for its complete virulence (Nagahashi et al 1998;Catlett et al 2003;Ma and Li 2012), only CaSLN1 is structurally and functionally similar to SLN1 of S. cerevisiae; however, the null mutation is not lethal (Ma and Li 2012). Similarly, in Aspergillus nidulans the gene tcsB was characterized and is similar in structure and function to SLN1 (Furukawa et al 2002), but as with CaSLN1, it does not appear to be essential in the osmotic stress response (Saito 2001;Furukawa et al 2002).…”
Section: Yeast and Fungimentioning
confidence: 99%
See 1 more Smart Citation